Rural women and poverty: A study on the role of RDRS for poverty alleviation in Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
No development objectives can be achieved without making women self reliant. The present study deals with the role of Rangpur Dinajpur Rural Service (RDRS) on poverty alleviation and women empowerment in Kaligonj upazila under Lalminirhat district considering their participation in different programmes of RDRS. The impact of the study was assessed in terms of economic and social gains accrued by the women's and their families' activities. The random sampling technique was used for selection of sample size. The test of mean difference, head count ratio, poverty gap, economic status index, social status index and decision-making index were used towards poverty alleviation and for women empowerment. The poverty situations improved as compared with that of the national level. It was clearly evident that participation in RDRS micro credit programmes, has substantially improved the respondent's economic condition, social condition and living standards. It referred the positive change in women empowerment in the study areas. By and large the women are better at present in respect of social awareness, freedom of attitude, financial freedom and exercising the right in decision making activities compared to their previous situation. It may , therefore, be inferred that the holistic approach followed by the RDRS for socioeconomic development led to increased family income, socioeconomic and decision making status in general and those of the women in particular in the study area. Keywords: Rural Women; Women empowerment; Poverty alleviation; RDRS DOI: 10.3329/jbau.v6i2.4842 J. Bangladesh Agril. Univ. 6(2): 415-421, 2008